A review of iron use and recycling in municipal wastewater treatment plants and a novel applicable integrated process. (July 2023) - Wu, Zhangsong; Ji, Shenghao; Li, Yu-You; Liu, Jianyong
Graphical abstract: Highlights: Use of iron in wastewater & sludge treatment in WWTPs & limitations are discussed. Methods of iron recovery from sludge and recycle in WWTPs are firstly reviewed. Acidification of digestate from AD-SR process can recover Fe & S simultaneously. An integrated process is proposed for energy, P recovery & Fe, S recycling. Fe dosage could be reduced to 4.2 mg/L with 80% sludge reduction & 60% P recovery. Abstract: Chemical methods are expected to play an increasingly important role in carbon-neutral municipal wastewater treatment plants. This paper briefly summarises the enhancement effects of using iron salts in wastewater and sludge treatment processes. The costs and environmental concerns associated with the widespread use of iron salts have also been highlighted. Fortunately, the iron recovery from iron-rich sludge provides an opportunity to solve these problems. Existing iron recovery methods, including direct acidification and thermal treatment, are summarised and show that acidification treatment of FeS digestate from the anaerobic digestion-sulfate reduction process can increase the iron and sulphur recycling efficiency. Therefore, a novel applicable integrated process based on iron use and recycling is proposed, and it reduces the iron salts dosage to 4.2 mg/L and sludge amount by 80%. Current experimental research and economic analysis of iron recycling show that this process has broad application prospects in resource recovery and sludge reduction.